2004
DOI: 10.1177/107110070402500706
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Painful Neuroma on the Lower Extremity by Resection and Nerve Stump Transplantation Into a Vein

Abstract: Lower extremity neuroma resection with nerve stump transposition into a vein was employed in eight patients (five male, three female). The neuromas resulted from amputations (four patients), vein stripping procedures (two patients), tumor resection, and toe-harvest for thumb reconstruction. Follow-up averaged 17 months (range, 8-37). Four of the patients experienced complete and permanent relief of pain; in three patients mild pain recurred within 3 months. All of these patients were satisfied with the result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Various techniques have been described to minimize neuroma formation with variable outcomes [4]–[7]. To date, the most promising and practical method of neuroma treatment has been surgical removal and transplantation of the nerve stump into a vein, the so-called nerve capping technique [4], [8]. However, its usage is limited by the size of available veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been described to minimize neuroma formation with variable outcomes [4]–[7]. To date, the most promising and practical method of neuroma treatment has been surgical removal and transplantation of the nerve stump into a vein, the so-called nerve capping technique [4], [8]. However, its usage is limited by the size of available veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Transection of a peripheral nerve may result in the formation of a painful neuroma and numerous surgical strategies have been proposed to prevent this occurrence. 3 In particular, previous evidences 12,14,15,20 have been published suggesting that veins could be used to prevent neuroma formation, and it has been demonstrated that burying transected nerve stumps into an adjacent vein left in place was an effective method in preventing neuroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve covering can be obtained either by burying the nerve stump into a nearby anatomic structure or by capping it with either biological or synthetic material. [7][8][9][10][11][12][13][14][15][16][17][18][19] Among the various attempts, burying of the nerve stump into an adjacent vein have been tested both experimentally 12,15,20 and with patients 10,11,13,14,21 with promising results. Vein tissue are used in nerve surgery also in case of nerve defects where free vein grafts can be used as conduits for bridging the gap.…”
mentioning
confidence: 99%
“…Among those studies presenting short-term results, there were three on neuroma resection and transposition of the proximal nerve stump into the lumen of a vein [2][3][4]. An experimental study and two of the clinical studies on this technique were published by the author [3][4][5].…”
Section: Introductionmentioning
confidence: 97%
“…An experimental study and two of the clinical studies on this technique were published by the author [3][4][5]. This retrospective study was conducted to evaluate the mid-term results of this method in part of the same patient group.…”
Section: Introductionmentioning
confidence: 99%